Unwillingness to pay for privacy: A field experiment - Alastair R. Beresford; Dorothea Kübler; Sören Preibusch (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We measure willingness to pay for privacy in a field experiment. Participants were given the choice to buy a maximum of one DVD from one of two online stores. One store consistently required more sensitive personal data than the other, but otherwise the stores were identical. In one treatment, DVDs were one Euro cheaper at the store requesting more personal information, and almost all buyers chose the cheaper store. Surprisingly, in the second treatment when prices were identical, participants bought from both shops equally often.
Keywords: C93; D12; 330; privacy; willingness to pay; field experiments; Datenschutz; Willingness to pay; Feldforschung